The Ramayana - Seeger, Elizabeth, 1889-; Valmiki. Ramayana; Laite, Gordon (London : J.M. Dent & Sons Ltd., 1969)
Relates the wanderings of Rama, the king's son and heir, during his fourteen years of banishment from his father's house.
Keywords: Mahabharata